EVALUASI POLA PERESEPAN PADA PASIEN LANJUT USIA MENGGUNAKAN WHO PRESCRIBING INDICATORS - Mia N. A. Fatin; ED. Y.M. Pasha; Khairunnisa Fadhilah; Vera L. Fitriani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Older patients are very susceptible to drug use problems. Drug use problems are related to physiological conditions that affect the pharmacokinetics and pharmacodynamics of the drug. This study aimed to evaluate drug prescribing pattern in older patients at Pasundan Health Center Bandung. Data were retrospectively collected from prescriptions from March to June 2021. The pattern of prescribing drugs was evaluate using the WHO prescribing indicator with five indicators: the number of drugs per prescription, antibiotic use, generic drugs, the percentage of injection preparations, essential drug use. A total of 638 prescriptions met the inclusion criteria. The average number of drugs per prescription is 2.8. The prescription drugs from a total of 1.777 drugs in the form of generic drugs amounted to 83.29%, and essential drugs amounted to 74.28%. The antibiotics and injection use percentage were 11.82% and 0%, respectively. The most frequently prescribed antibiotics were amoxicillin, clindamycin, ciprofloxacin, betamethasone, and miconazole. The most frequently prescribed drugs were amlodipine, paracetamol, diclofenac sodium, chlorpheniramine maleate, and multivitamins. The use of essential and generic drugs was below WHO standard, while the average number of drugs per prescription was above WHO standard.